2017
DOI: 10.1002/mrd.22826
|View full text |Cite
|
Sign up to set email alerts
|

Ssm1b expression and function in germ cells of adult mice and in early embryos

Abstract: Ssm1b (Strain-specific modifier of DNA methylation 1b) is a Krüppel-associated box (KRAB) zinc finger gene that promotes CpG methylation in the mouse transgene HRD (Heavy chain enhancer, rearrangement by deletion). We report here that Ssm1b expression and concomitant HRD methylation are also present in the male and female germ cells of adult mice. Ssm1b is expressed in both diploid (2N) and haploid (1N) oocytes, as well as in 1N spermatids and spermatozoa, but not in 2N spermatogonia. Interestingly, Ssm1b mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Zfp982 has previously been shown to be involved in cell lineage differentiation in embryogenesis [ 58 ] and the 12-fold decrease in levels of this factor in our DKO mice may have significantly disrupted developmental processes. Zfp979 (also known as Ssm1b ) initiates DNA methylation and inhibits transcription in undifferentiated embryonic stem cells as well as in adult murine germ cells [ 59 ]. The 20-fold decrease of Ssm1b seen in our DKO testes could allow expression of a multitude of proteins detrimental to early development and germ cell maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Zfp982 has previously been shown to be involved in cell lineage differentiation in embryogenesis [ 58 ] and the 12-fold decrease in levels of this factor in our DKO mice may have significantly disrupted developmental processes. Zfp979 (also known as Ssm1b ) initiates DNA methylation and inhibits transcription in undifferentiated embryonic stem cells as well as in adult murine germ cells [ 59 ]. The 20-fold decrease of Ssm1b seen in our DKO testes could allow expression of a multitude of proteins detrimental to early development and germ cell maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Ssm1b was originally identified due to the differential methylation of the HRD transgene in B6J (methylated) and DBA (unmethylated) genetic backgrounds. In total, when maintained on an F1 background with DBA or SJL, the HRD transgene is methylated in seven strains of mice (C57BL/6J, FVB/NJ, C57L/J, LP/J, 129/SvJ, BALB/cJ, and A/J) and unmethylated in six strains of mice (DBA/2J, C3H/HeJ, SJL/J, CBA/J, SM/J, and AKR/J) [ 108 ]. The reference genomes for 16 strains were recently generated but there remain significant gaps in this region, likely due to the repetitive nature of the KRAB-ZFPs within this cluster, which are predicted to have arisen through segmental gene duplications [ 17 , 59 , 109 ].…”
Section: Lessons From Transgenesmentioning
confidence: 99%
“…Finally, it was previously suggested that CRISP‐3 may modulate the activity of other genes either at the expression or at the functional level which, in turn, may control cell invasion in prostate cancer (Pathak et al ., ). This suggested gene expression modulation is important because alterations in gene expression can alter sperm function and quality (Castaneda et al ., ; Ratnam et al ., ). Indeed, in our study, varicocoele was associated with a decrease in seminal and functional quality of spermatozoa, when compared with controls group.…”
Section: Discussionmentioning
confidence: 97%